Microstructure determination of hydroxy-terminated polybutadiene based polyurethane using Fourier transform infrared spectroscopy - Marta Ferreira Koyama Takahashi; Milton Faria Diniz (Eclética Química, 2018)
A evaluation of microstructure of the flexible segment of a PBLH-based polyurethane was done by FTIR analysis, employing the technique of pellet with potassium bromide.